Business plans handbook : a compilation of business plans developed by individuals throughout North America. Volume 16 - 4 0 16; Pearce, Lynn M.; 5 (Farmington Hills, MI : Gale Cengage Learning, 2010)
Actual business plans compiled by, and aimed at, entrepreneurs seeking funding for small businesses. Presents sample plans taken from businesses in the manufacturing, retail and service industries which serve as examples of how to approach, structure and compose business plans.
Automated teller machines;Bed & Breakfast: Rocheport Bed and Breakfast --;Beekeeping business: B. Strand's Bees --;Car wash and car detailing business: Wash and Go --;Counseling practice: Roper Counseling Services, Inc. --;Custom carpentry shop: Choice Cut Carpentry, Inc. --;Day camp organizer: Camp in the Park --;Diner: Shoestrings --;Domestic services provider: Helping Hands Personal Services, LLC --;Energy efficiency auditing firm: Energy Physicians --;Gift shop: The Busy Bee --;Home organization service: Break Free Organizing --;House cleaning: Mid-Missouri Maid Service --;Ice cream parlor: SonnyScoops --;Nature photography business: Shutterbugs, Inc. --;Online party-planning company: Theme Party in a Box --;Organic cleaning supplies: Green Home Care Solutions --;Physical therapy practice: Healing Hands Physical Therapy, Inc. --;Stable: Miller Stables --;Wine storage: Wine Portfolio, Inc. --;Appendixes: Business plan template --;Fictional plans: Food distributor --;Hardware store --;Associations --;Consultants --;SBA regional offices --;Small business development centers --;Service Corps of Retired Executives offices --;Venture capital & financing companies --;Glossary of small business terms. (ATMs): Quick cash services --
ISSN 1084-4473.
Keywords: 2 -- 0; 6; Planning;Planning;Information services -- Small business;Business planning;Small business;New business enterprises;Entrepreneurship -- 20 -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Directories.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2